Pharmacokinetics of betamethasone and betamethasone 17-monopropionate in Chinese healthy volunteers after intramuscular injection of betamethasone phosphate/betamethasone dipropionate - He, Chunhui; Fan, Hongwei; Tan, Jie; Zou, Jianjun; Zhu, Yubing; Yang, Kun; Hu, Qin (Arzneimittelforschung, 2011)
The aim of this study was to evaluate the pharmacokinetic profiles of betamethasone (BOH, CAS 378-44-9) and betamethasone 17-monopropionate (B17P), the active metabolites of betamethasone phosphate (BSP) and betamethasone dipropionate (BDP), respectively, after administration of betamethasone i. m. (BSP 2 mg and BDP 5 mg). After ten healthy volunteers had received a singledose intramuscular adminitration of betamethasone i. m., blood samples were collected pre-dose and for 336 h postdose. The plasma levels of B17P and BOH were measured by liquid chromatography-tandem mass spectrometry (LC-MS/ MS). When compared to ΒΟΗ, Β17Ρ exhibited a longer time to maximum concentration (15.0 ± 9.0 h vs. 2.8 ± 1.7 h), a lower Cmax (0.6 ± 0.2 ng/mL vs. 14.5 ± 3.7 ng/mL), and a much longer half-life (80.8 ± 22.7 h vs. 9.6 ± 3.6 h). Betamethasone i. m. produced rapid onset and sustained action through an initial rapid-increased plasma concentration of BOH and a sustained plasma concentration of B17P, respectively.
Keywords: Betamethasone; Betamethasone dipropionate; Betamethasone 17-monopropionate; Intramuscular administration; Pharmacokinetics